Efektivitas Himbauan Mengenakan Jilbab dalam Rangka Pengembangan Rasa Keberagamaan Siswi SMA 1 Sleman - Wakhid Hasyim (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2016)
This research is a field research and it is done without treatment (naturalistic). To get a depth data this research used qualitative approach. Reseacher use observation methode, interview and documentation to collect data. This research refers to the policy of one of the Islamic Study teacher in senior high school (not Islamic high school). The teacher obliged students (especially girls) to wear veil during his subjects. At another learning subject, Students are free to wear the veil or not. The aim of this research is describing and analyzing that policy and the influence of the policy to the religious consciousness of students. To analyze the long-term effects, reseacher made the alumni to be subject of this research, because they have experienced the policy before.